2011
DOI: 10.1038/modpathol.2011.8
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 and ALDH-1 mark breast epithelium at risk for breast cancer development

Abstract: It is well established that benign proliferative lesions and atypical hyperplasia increase the risk of breast cancer, which can develop in either breast. At present, there is no radiological, pathological, or molecular marker capable of distinguishing which proliferative or atypical lesions will progress to carcinoma. EZH2, a protein involved in stem cell renewal and carcinogenesis is upregulated in the morphologically normal breast epithelium from BRCA1 mutation carriers. Here, we tested the hypothesis that E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 32 publications
3
56
0
Order By: Relevance
“…EZH2 is associated with younger age at breast cancer diagnosis (29), increased tumor size, high histopathologic grade, negative hormone receptor status, epidermal growth factor receptor and Her2 overexpression, p53 mutations, lymphatic invasion, poor survival and metastasis (30)(31)(32). Our results demonstrated that EZH2 activity was associated with lung metastasis in a model of basal breast cancer.…”
Section: Discussionmentioning
confidence: 47%
“…EZH2 is associated with younger age at breast cancer diagnosis (29), increased tumor size, high histopathologic grade, negative hormone receptor status, epidermal growth factor receptor and Her2 overexpression, p53 mutations, lymphatic invasion, poor survival and metastasis (30)(31)(32). Our results demonstrated that EZH2 activity was associated with lung metastasis in a model of basal breast cancer.…”
Section: Discussionmentioning
confidence: 47%
“…This implies that EZH2 expression is related to tumor invasion and metastasis (Visser et al, 2001;Hoffmann et al, 2007;Kunju et al, 2011). Bachmann et al (2006) and Zhang et al (2006) also demonstrated that EZH2 promoted the occurrence, development, and invasion of endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Kunju et al (2011) in very recent study presented primary evidence that epithelial and stromal ALDH1 detection in benign breast biopsies may predict increased risk for breast cancer, which may have implications for breast cancer prevention.…”
Section: Discussionmentioning
confidence: 99%